Small and medium enterprise agro-processing firms supply chain~performance: The role of~owner-manager's managerial competencies, information sharing and information quality - Sheila Namagembe; Musa Mbago (Modern Supply Chain Research and Applications, 2023)
Purpose - The study examined the influence of small and medium enterprise (SME) owner-managers' managerial competencies on supply chain performance, the mediation role of information quality on the SME owner-managers' managerial competencies and supply chain performance relationship, the mediating role of information quality on the information sharing and supply chain performance relationship and the mediating role of both information sharing and information quality on SME owner-managers' managerial competences and supply chain performance relationship. Design/methodology/approach - Data were collected from SME agro-processing firms. The determined sample size for the agro-processing firms was 200, while an effective sample size of 177 was obtained. The Covariance Structural Equation Modelling software was used to obtain results on the influence of SME owner-managers' managerial competencies on supply chain performance, the mediation role of information quality on the SME owner-managers' managerial competencies and supply chain performance relationship, the mediating role of information quality on the information sharing and supply chain performance relationship and the mediating role of both information sharing and information quality on SME owner-managers' managerial competences and supply chain performance relationship. Findings - Findings indicated that a positive significant influence of SME owner-managers' managerial competencies on supply chain performance and the presence of partial mediation effects when the mediating role of information quality in the SME owner-managers' managerial competencies and supply chain performance relationship and the information sharing and supply chain performance relationship is tested. Also, a partial mediating role of information sharing and information quality is obtained in the SME owner-managers' managerial competencies and supply chain performance relationship. Research limitations/implications - The study mainly focused on SME agro-processing firms eliminating other SME manufacturing firms. Also, the research employed a wholistic approach when studying the SME agro-processing firms without focusing on how SME owner-managers' managerial competencies would affect information sharing, information quality and supply chain performance based on the market type (local or foreign) and the source of raw materials (local or foreign) and the impact of information sharing on information quality hasn't been given significant attention in the existing literature. Originality/value - The research focused on the mediation role of quality of information shared by SME owner-managers in the relationship between information sharing and supply chain performance, the mediating role of information quality in the SME owner-managers' managerial competencies and supply chain performance and the mediating role of both SME owner-manager's information sharing and quality of information shared in the relationship between SME owner-managers' managerial competences and supply chain performance. These mediation effects haven't been given significant attention in previous research. Further, while information sharing and information quality have been studied, they have been studied at a supply chain level, not at a managerial level.
Keywords: 650; Information quality; Information sharing; Owner-manager managerial competencies; Small and medium enterprises (SMEs); Supply chain performance